Characterization of a STAT-1 Knockout Mouse Model for Machupo Virus Infection and Pathogenesis - Stephanie R. Monticelli; Ana I. Kuehne; Russell R. Bakken; Susan R. Coyne; Kenise D. Lewis; Jo Lynne W. Raymond; Xiankun Zeng; Joshua B. Richardson; Zebulon Lapoint; Jennifer L. Williams; Christopher P. Stefan; Jeffrey R. Kugelman; et al. (Viruses)
Machupo virus (MACV), a member of the Arenaviridae family and causative agent of Bolivian hemorrhagic fever, results in lethality rates of 25–35% in humans. Mice lacking the signal transducer and activator of transcription 1 (STAT-1−/−) have previously been shown to succumb to MACV infection within 7–8 days via the intraperitoneal route. Despite these reports, we observed partial lethality in STAT-1−/− mice following challenge with wild-type MACV. Serial sampling studies to evaluate the temporal progression of infection and pathologic changes after challenge revealed a two-phase disease course. The first phase was characterized by viral load and pathological lesions in the spleen, liver, and kidney followed by a second, lethal phase, defined by high viral titers and inflammation in the brain and spinal cord resulting in neurological manifestations and subsequent mortality. Tissue adaptation in the brains of challenged STAT-1−/− mice resulted in a fully lethal model in STAT-1−/− mice (mouse-adapted; maMACV). A similar two-phase disease course was observed following maMACV challenge, but more rapid dissemination of the virus to the brain and overall pathology in this region was observed. The outcome of these studies is a lethal small rodent model of MACV that recapitulates many aspects of human disease.